SOCIAL STRUCTURE OF COMMUNITIES RESIDING IN DISASTER-PRONE AREAS: A CASE STUDY OF BUMI WARAS SUB-DISTRICT, BANDAR LAMPUNG CITY" - Fathurrahman,; Alvianti, Vivian; Saraswati, Zenia F; Ibad, Muhammad Zainal (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
The continuous increase in the population of Bandar Lampung can lead to excessive land use. This trend results in residents choosing to live in suburban areas that are vulnerable to disasters and climate change. The social bonds among individuals in the study area may encourage them to remain or stay in areas prone to tidal flooding and tsunamis. This research employs social network analysis to identify the social structure of communities residing in disaster-prone coastal areas. There are 18 communities classified into 10 types of organizations. These communities have the potential to improve their living conditions rather than merely coping with increasing disasters year by year. The kelurahan (urban village) of Bumi Waras and Kelurahan have moderate centrality values ranging from 0.34 to 0.66. Key actors, such as Tarmizi, Anang Firmansyah, and Fitriani, with high centrality, play central or key roles. In facing the risks of tidal flooding and tsunamis, enhancing community resilience is crucial, which can be achieved through physical and social approaches with an active role of the government in strengthening social bonds, improving information flow, and involving influential local actors to build comprehensive disaster resilience.